Transformações pessoais : no embalo das danças circulares sagradas e o reencontro com a natureza do ser - Madalóz, Rodrigo José (2016)
SELF TRANSformACTION (TRANSformAÇÕES pessoais): on the circular rythm the recover with the nature of being" was a study wich followed a guided research style in seven interventions with two distinct groups: the first femenine genre, composed by educators in training working in public school on the region of the Missões (RIO GRANDE DO SUL / BRAZIL); the second group, of both genders, with participants from the elderly group of institutional program of a University in Missões. First this research aimed to investigate the meaning of Circular Sacred Dances (CSD) in the educational process. As secondary objectives: facilitate the practice of CSD as a education workshop for two distinct groups; understand the dance and its educational dimension in formal and non-formal settings; establish listening position, analysis and interpretation before the insertion of CSD in different educational spaces; and link the CSD to the culture of peace. The sample included eight participants, all female, chosen intentionally by the frequency and interaction on the meetings: Four teachers from public school and four participants from the institutional project. The weekly meetings were divided into three stages: awareness, the circles and the farewell. The research was guided by a qualitative approach, supported by a worldview based on the paradigm Symbiosynergic and Inventive (BERTRAND; VALOIS, 1994) and valued by a reflective / interpretative style set on hermeneutic and phenomenology. Diary and oral phenomenological interview, individual and open, recorded and then transcrited were used to gather information. The triggering question of the interview was: what meaning it had for you to join the CSD workshop? For the organization and understanding of information, it was applied the phenomenological method proposed by Giorgi (2009, 2010) and Comiotto (1992). The following steps were followed until the phenomenological essences be achieved: the meaning of the whole; the units of meaning; participants expressions transformation in psychosensitive expressions; synthesis of meaning structures; and phenomenological dimensions. The application of the phenomenological method emerged the following essences and dimensions that answered the guiding question and the proposal of the thesis: GROUP IMPORTANCE (host and approach; care of themselves and each other, trust and feel part of the group); BE SENSITIVE, EMOTIONS AND FEELINGS ((re) meet, strengthen and celebrate; whole and entire, paths to peace); CHILDHOOD AND ADOLESCENT (memories, being child and adolescent: laughs and cries, play, toys and games); CIRCULAR AND SPIRITUALITY DANCE (mandala: exterior and interior relationship; energy circle: dense and subtle, dance and meditation). The meanings given by the participants from the CSD workshop reaffirm the potential that dances have for the educational process in formal and non-formal spaces as possible the practice of CSD in the form of esthetic education workshop for the participating groups, as it was possible to understand the dance and its educational dimension in formal and non-formal context, establishing a listening position, understanding and interpretating before the insertion of CSD in different educational spaces as potentiator and source of culture and education to peace from an esthetic worldview guided training for sensitivity, which perceives human beings (men and women) as participants in the teachinglearning process. By offering the experience of CSD in formal and non-formal spaces, CSD acted as potentiating a culture of peace and non-violence.